2017
DOI: 10.1021/acsphotonics.7b00610
|View full text |Cite
|
Sign up to set email alerts
|

Can Ultrastrong Coupling Change Ground-State Chemical Reactions?

Abstract: Recent advancements on the fabrication of organic micro-and nanostructures have permitted the strong collective light-matter coupling regime to be reached with molecular materials. Pioneering works in this direction have shown the effects of this regime in the excited state reactivity of molecular systems and at the same time have opened up the question of whether it is possible to introduce any modifications in the electronic ground energy landscape which could affect chemical thermodynamics and/or kinetics. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
135
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 60 publications
1
135
0
Order By: Relevance
“…In recent years, strong coupling to organic materials has received great attention for its potential to greatly influence fundamental features of the underlying organic molecules such as their optical response [5][6][7], transport properties [8][9][10][11][12], or chemical reactivity [13][14][15]. In particular, the potential of polaritonic chemistry, i.e., the ability to influence the chemical structure and reactions of organic compounds through coupling to a cavity, has attracted a lot of interest [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, strong coupling to organic materials has received great attention for its potential to greatly influence fundamental features of the underlying organic molecules such as their optical response [5][6][7], transport properties [8][9][10][11][12], or chemical reactivity [13][14][15]. In particular, the potential of polaritonic chemistry, i.e., the ability to influence the chemical structure and reactions of organic compounds through coupling to a cavity, has attracted a lot of interest [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Cavity-induced modifications to the ground state have also been theoretically studied. In particular, for model molecules without ground-state dipole moments and only electronic dipole transitions, it has been shown that there is no collective enhancement of energy shifts [17], and more specifically, that chemical reactions are not strongly modified even under ultrastrong collective coupling [30]. In a series of papers based on more microscopic models, Flick and co-workers have shown that ground state properties can be significantly modified under single-molecule (ultra-)strong coupling [18,25,26], but have not treated chemical reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Describing the photon-matter interaction with the tool of cavity quantum electrodynamics is an emerging field. It has been successfully demonstrated both experimentally [26][27][28][29][30][31][32] and theoretically [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], that the quantized photonic mode description of the electromagnetic field can provide an alternative solution for studying adequately the light-molecule's OPEN ACCESS RECEIVED…”
mentioning
confidence: 99%
“…This means that the quantum yield ϕ ¼ N prod =N phot of the reaction, which describes the percentage of molecules that end up in the desired reaction product per absorbed photon, has a maximum value of 1. This limit can be overcome in some specific cases, such as in photochemically induced chain reactions [2-4], or in systems that support singlet fission to create multiple triplet excitons (and thus electron-hole pairs) in solar cells [5,6].Polaritonic chemistry, i.e., the potential to manipulate chemical structure and reactions through the formation of polaritons (hybrid light-matter states) was experimentally demonstrated in 2012 [7], and has become a topic of intense experimental and theoretical research in the past few years [8][9][10][11][12][13][14][15][16][17][18]. However, existing applications and proposals have been limited to enhancing or suppressing the rates of single-molecule reactions.…”
mentioning
confidence: 99%
“…Polaritonic chemistry, i.e., the potential to manipulate chemical structure and reactions through the formation of polaritons (hybrid light-matter states) was experimentally demonstrated in 2012 [7], and has become a topic of intense experimental and theoretical research in the past few years [8][9][10][11][12][13][14][15][16][17][18]. However, existing applications and proposals have been limited to enhancing or suppressing the rates of single-molecule reactions.…”
mentioning
confidence: 99%